Proceedings of the 2009 Conference on Empirical Methods in Natural Language Processing Volume 3 - EMNLP '09 2009
DOI: 10.3115/1699648.1699684
|View full text |Cite
|
Sign up to set email alerts
|

Convolution kernels on constituent, dependency and sequential structures for relation extraction

Abstract: This paper explores the use of innovative kernels based on syntactic and semantic structures for a target relation extraction task. Syntax is derived from constituent and dependency parse trees whereas semantics concerns to entity types and lexical sequences. We investigate the effectiveness of such representations in the automated relation extraction from texts. We process the above data by means of Support Vector Machines along with the syntactic tree, the partial tree and the word sequence kernels. Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…A recent approach successfully employs a convolution tree kernel over constituent syntactic parse tree [42,46]. The combination of such kernel with others based on grammatical relations from dependency structure was successfully modeled in [30].…”
Section: Related Workmentioning
confidence: 99%
“…A recent approach successfully employs a convolution tree kernel over constituent syntactic parse tree [42,46]. The combination of such kernel with others based on grammatical relations from dependency structure was successfully modeled in [30].…”
Section: Related Workmentioning
confidence: 99%
“…To adapt the tree kernel to medical domain, we followed the approach in (Nguyen et al, 2009) to take the syntactic structures into consideration. We also added the argument types as features to the tree kernel.…”
Section: Baseline Approachesmentioning
confidence: 99%
“…Moreover, Moschitti et al in [79] suggested the combination of constituent and dependency parse trees to represent the syntax of a sentence for relation extraction. This idea was continued to improve by augmenting the semantics concerning to entity types and lexical sequences ( [83]). Recently, Reichartz et al in [88] have proposed a novel method of using typed dependency parse trees which include labeled edges and nodes.…”
Section: Supervised Approachmentioning
confidence: 99%
“…In other words, the problem of relation extraction is formulated as a classification problem and relations of unseen entity pairs are classified by a target function which is learnt from a manually labeled training dataset. Previous study applied Support Vector Machine (SVM) ( [18], [79], [83], [87], [88]) to learn the target function from training data and used it to determine the label of the relation between novel entity pairs in the sentence. …”
Section: Supervised Approachmentioning
confidence: 99%
See 1 more Smart Citation